Copies of the treaties, made 3rd and 21st August, 1871, between Her Majesty the Queen and the Chippewa and Cree Indians of Manitoba and country adjacent. - Great Britain.; Cree Indians. Treaties, 1871.; Chippewa Indians. Treaties, 1871. (Ottawa, I.B. Taylor, 1873)
Cover-title. Mode of access: Internet.